Adapting the Home - Martie Gillen; Pat J. Dasler; Jenny Jump (EDIS)
This revised 4-page fact sheet discusses AARP’s 10 basic ideas to increase home safety, how to individualize for each person or activity, how to apply universal design to make homes safer, and assistive devices. Written by Martie Gillen, Pat J. Dasler, and Jenny Jump, and published by the UF Department of Family, Youth and Community Sciences, November 2012.